A short history of Byzantium - Norwich, John Julius, 1929- (Penguin, 1998)
Brings together some of the events from the author's trilogy about the rise and fall of the Byzantine empire. With wit, intelligence and his trademark eye for riveting detail, John Julius Norwich has brought together the most important and fascinating events from his trilogy of the rise and fall of the Byzantine empire